PENGARUH PEMBERIAN EDUKASI KESEHATAN TERHADAP TINGKAT KECEMASAN PADA PASIEN YANG MENJALANI HEMODIALISA DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Manurung, Rostinah; Manurung, Nixson; T. Bolon, Christina Magdalena; Dewi, Ratna; Siregar, Sarmaida (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Hemodialysis is a therapy for Chronic Kidney Failure (CKD) patients to replace kidney function using an artificial kidney in the form of a dialysis machine. Hemodialysis patients will experience lifelong dependence, this will result in imbalanced changes in their lives, these changes will give rise to physical and psychological problems, one of which is anxiety. Health education is a planned effort to influence other people to carry out what is expected. The aim of this research was to determine the effect of providing health education using leaflets on the anxiety level of hemodialysis patients at the Imelda Workers Indonesia General Hospital, Medan. The method used is correlative descriptive. The number of samples in this study was 38 respondents using a purpose sampling technique. The results of the research using the Wilcoxon statistical test resulted in a p-value of 0.00 with a significance of p < (0.05) p-value of 0.00 < 0.05. The conclusion obtained was that providing health education using leaflet media influenced the anxiety level of Chronic Kidney Failure (CKD) patients undergoing hemodialysis at the Imelda Workers Indonesia General Hospital, Medan